Physicochemicals, Organoleptic Properties, and Nutritional Adequacy Rates of Supplementary Food Cookies with the Addition of Whey Protein Powder, a By-Product of Making Dangke - Muh Achyar Ardat; Ekajayanti Kining; Zakiah Wulandari; Irma Isnafia Arief; Nur Afni (Jurnal Ilmu Pertanian Indonesia, 2025)
The purpose of this research is to develop a supplementary meal for breast milk (CF) using whey protein derived from the byproduct of dangke manufacture, a typical Enrekang dish. The research involved spray drying whey protein powder and making CF cookies with four different whey protein powder addition treatments (0, 10, 20, and 30%). The physicochemical parameters of whey protein powder were studied, and the sensory and nutritional properties of CF cookies were evaluated. A sensory evaluation of the CF cookies found that 20% whey protein powder produced the best results in terms of color, flavor, and texture. Cookies made with 20% whey protein contained 6.80% protein, 22.25% total fat, 65.98% carbohydrate, and a total energy value of 490.73 Kcal/100g. While whey protein cookies contain protein and energy benefits that are comparable with WHO recommendations for CF, some concerns require attention. The total sugar level (24.625%) and salt content (453.67 mg/100 g) were relatively high, necessitating modifications to meet the sugar and sodium limits in CF. This work demonstrates the potential use of whey protein obtained from dangke by-products as a CF ingredient; nevertheless, more refinement is required to optimize its compliance with infant nutritional requirements. Keywords: complementary food, Enrekang, local food, milk, whey protein